Influence of the scanning resolution on image segmentation accuracy for an objective fold cracking evaluation - Pál, Magdolna; Novaković, Dragoljub; Pavlović, Živko; Dedijer, Sandra (Univerzita Pardubice, 2013)
The fold cracking resistance of coated papers has become an important field of investigation, due to the constant production cost optimization in paper industry. Although the fold cracking of coated papers is an important phenomenon, there is no standardized method for quantitative evaluation of the amount of cracking, just a few, newly proposed methods. These methods are based on digital image analysis, with different sample preparation, image pre- and post-processing and evaluation techniques. One of the differences is the resolution of digitalized samples. This paper presents an analysis of the effects of chosen digitalisation resolution of paper samples on the image analysing accuracy for an objective fold cracking evaluation. In order to get more insight, a detailed investigation has been conducted to overview the advantages and disadvantages of higher resolution of scanned samples in the objective fold cracking evaluation process.
Keywords: fold cracking; image resolution; quality control